2008
DOI: 10.1111/j.1462-2920.2008.01664.x
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli O157 can grow in natural freshwater at low carbon concentrations

Abstract: Whereas much information on the die-off of Escherichia coli in the aquatic environment is available, only few data support its growth under such conditions. We therefore investigated batch growth in microcosms containing different types of sterile freshwater. The water samples were inoculated with low starting cell concentrations of E. coli O157 (3 x 10(3) cells ml(-1)) and growth was followed using nucleic acid staining combined with flow cytometry. We demonstrated that E. coli O157 is able to grow in sterile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
86
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 61 publications
7
86
0
Order By: Relevance
“…Furthermore, E. coli was also found to exhibit a high degree of catabolic flexibility, which conferred a clear fitness advantage in its secondary habitats such as soil and water (Ihssen and Egli, 2005). E. coli O157:H7 may survive and even grow in sterile freshwater at low carbon concentrations, which stands in contrast to the common conception that the organism will die out over time in such strongly carbon-limited environments (Vital et al, 2008). Moreover, because of the production of RpoS (subunit of RNA polymerase, represents a major factor involved in starvation survival), E. coli is able to rapidly adapt to, and tolerate, diverse stress conditions (Lange and Hengge-Aronis, 1991).…”
Section: E Coli Fate In Natural Habitatsmentioning
confidence: 60%
See 1 more Smart Citation
“…Furthermore, E. coli was also found to exhibit a high degree of catabolic flexibility, which conferred a clear fitness advantage in its secondary habitats such as soil and water (Ihssen and Egli, 2005). E. coli O157:H7 may survive and even grow in sterile freshwater at low carbon concentrations, which stands in contrast to the common conception that the organism will die out over time in such strongly carbon-limited environments (Vital et al, 2008). Moreover, because of the production of RpoS (subunit of RNA polymerase, represents a major factor involved in starvation survival), E. coli is able to rapidly adapt to, and tolerate, diverse stress conditions (Lange and Hengge-Aronis, 1991).…”
Section: E Coli Fate In Natural Habitatsmentioning
confidence: 60%
“…General observations on E. coli survival E. coli can, to varying extents, survive in different open environments such as soil, manure and water (Kudva et al, 1998;Jiang et al, 2002;Vital et al, 2008). There are also possibilities for migration between these habitats.…”
Section: Factors Affecting E Coli Fate In Open Environmentsmentioning
confidence: 99%
“…Another possible explanation is the release of extracellular DNA from particulate material during this initial period, which then becomes available for qPCR later. The increase in DNA amplified by both PMA-qPCR and qPCR under dark conditions was not surprising because the availability of dissolved organic carbon can trigger the growth of Enterococcus, which subsequently ceases when the nutrients are depleted, as reported for the growth of Enterococcus in beach sands (51) and of E. coli O157 in natural freshwater at low carbon concentrations (43). The slopes from the cultivation-dependent method and PMA-qPCR were significantly different (P values ϭ 0.001 and 0.02 for sunlight exposure and dark condition, respectively), which was likely due to the presence of intact but noncultivable Enterococcus cells.…”
Section: Discussionmentioning
confidence: 97%
“…Vital et al (2008) similarly found a positive correlation between AOC and final concentration after a 3 day incubation.…”
Section: Discussionmentioning
confidence: 51%
“…AOC concentrations above 100 µg/mL are significant because they can lead to biological growth of harmful pathogens such as cholera (Vital et al , 2007) or E. coli (Vital et al , 2008). 50% (n = 8) of the samples had AOC concentrations higher than this value.…”
Section: Discussionmentioning
confidence: 99%